This is us. The complete second season [videorecording (DVD)] - Fogelman, Dan (Twentieth Century Fox Home Entertainment, 2018)
Chronicles the Pearson family across the decades, from Jack and Rebecca as young parents in the 1980s to their 37 year old kids Kevin, Kate and Randall searching for love and fulfillment in the present day. This grounded, life affirming dramedy reveals how the tiniest events in people's lives impact who they become, and how the connections they share with each other can transcend time, distance, and even death.